Prohibition, Stare Decisis, and the Lagging Ability of Science to Influence Criminal Procedure - Oliver, Wesley M. (2015)
Science has revealed that, contrary to longstanding intuitions, eyewitnesses are sometimes mistaken and false confessions do occur. The methods police use to obtain identifications and confessions can affect their reliability. Yet criminal procedure does not deter investigatory methods that produce unreliable evidence as thoroughly as it does those methods that produce reliable evidence. If an officer conducts an illegal search of a car trunk, the evidence is excluded and subsequently officers know that they must follow the rules if they hope to admit the fruits of such searches. If, however, an officer creates a suggestive lineup—which risks a false conviction—the identification from this lineup is not necessarily excluded. Interrogation methods that risk unreliable confessions are not even a concern for the rules of criminal procedure unless the suspect’s will is overborn, or the suspect has not agreed to be interrogated. The explanation for this state of affairs appears to be historical. Our rules of criminal procedure largely derive from the era of Prohibition, when searches for reliable evidence were society’s primary concern. Now that wrongful conviction is at least as great a concern as unreasonable searches, the law should acknowledge the need to deter police practices that risk the collection of unreliable evidence